The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0153575
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Clustering of Mycobacterium tuberculosis Complex Genotypes in Florida: Genetic Diversity Segregated by Country of Birth

Abstract: BackgroundTuberculosis (TB) is caused by members of the Mycobacterium tuberculosis complex (MTBC). Although the MTBC is highly clonal, between-strain genetic diversity has been observed. In low TB incidence settings, immigration may facilitate the importation of MTBC strains with a potential to complicate TB control efforts.MethodsWe investigated the genetic diversity and spatiotemporal clustering of 2,510 MTBC strains isolated in Florida, United States, between 2009 and 2013 and genotyped using spoligotyping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…A study from Canada used this method to reveal a complex coexistence of spatial and cohort clustering with the time of 1990 to 2013, and provided the basis for public health response [ 30 ]. Studies from Ghana [ 31 ] and American [ 32 ] about Mycobacterium tuberculosis strains or genotypes also found the spatio-temporal characteristics based on this method, which could guide the formulation of TB control and prevention policies. Though there were several studies in China have explored the distribution of TB, they were only restricted to a certain province or certain area, or the nationwide research just at the provincial level not the prefecture level.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Canada used this method to reveal a complex coexistence of spatial and cohort clustering with the time of 1990 to 2013, and provided the basis for public health response [ 30 ]. Studies from Ghana [ 31 ] and American [ 32 ] about Mycobacterium tuberculosis strains or genotypes also found the spatio-temporal characteristics based on this method, which could guide the formulation of TB control and prevention policies. Though there were several studies in China have explored the distribution of TB, they were only restricted to a certain province or certain area, or the nationwide research just at the provincial level not the prefecture level.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that genetic diversity and genomic plasticity in bacteria increase with geographic distance ( 32 34 ), which can make it difficult to perform SNP-based analyses ( 35 ). As expected, the reference-free analysis and pipeline applied here were not affected by high levels of nucleotide diversity and identified over 4,000 shared, homologous, protein-coding genes, which enabled the construction of a high-resolution phylogenetic tree with high levels of statistical support for several clades.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tools that allow characterization and genotypic analysis of TB, such as 24-locus mycobacterial interspersed repetitive unit-variable-number tandem-repeat (MIRU-VNTR) and spacer oligonucleotide typing (spoligotyping), allow an understanding of the dynamics and complexity of the population structure of Mycobacterium tuberculosis within a population [ 3 , 4 ]. These procedures allow identification of the different lineages in circulation within specific regions and their relationship with potential pathogenicity and virulence [ 5 , 6 ] Also, several reports from different geographic regions have described the levels of association with demographic, epidemiological and drug resistance characteristics [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%